Concurrent Strength and Endurance Training: The Influence of Dependent Variable Selection - Leveritt, M.; Abernethy, P. J.; Barry, B.; Logan, P. A. (The Journal of Strength and Conditioning Research, 2003)
Twenty-six active university students were randomly allocated to resistance (R, n = 9), endurance (E, n = 8), and concurrent resistance and endurance (C, n = 9) training conditions. Training was completed 3 times per week in all conditions, with endurance training preceding resistance training in the C group. Resistance training involved 4 sets of upper- and lower-body exercises with loads of 4-8 repetition maximum (RM). Each endurance training session consisted of five 5-minute bouts of incremental cycle exercise at between 40 and 100% of peak oxygen uptake (O2peak). Parameters measured prior to and following training included strength (1RM and isometric and isokinetic [1.04, 3.12, 5.20, and 8.67 rad·s1] strength), O2peak and Wingate test performance (peak power output [PPO], average power, and relative power decline). Significant improvements in 1RM strength were observed in the R and C groups following training. O2peak significantly increased in E and C but was significantly reduced in R after training. Effect size (ES) transformations on the other dependent variables suggested that performance changes in the C group were not always similar to changes in the R or E groups. These ES data suggest that statistical power and dependent variable selection are significant issues in enhancing our insights into concurrent training. It may be necessary to assess a range of performance parameters to monitor the relative effectiveness of a particular concurrent training regimen.